Design of a Mobile Application for Wireless Network Monitoring Based on Android - Mahfudzin, Abdul Halim; Widiantoko, Ari; Sudibyo, Novi Herawadi (Prosiding International conference on Information Technology and Business (ICITB), 2023)
Information and communication technology that is increasingly widespread today uses a computer network system as a medium for transforming information and data. One of the common network utilizations today is a wireless network using Wi-Fi (Wireless Fidelity) technology. The problem experienced at Junior High School Muhammadiyah 3 Metro is that the network administrator still uses a simple way of checking the network connection, namely by pinging the hosts connected to the network. The goal that the authors achieve is to monitor data traffic on wireless internet networks by designing Android applications as network controllers. With this problem, the authors made a thesis with the title "Designing an Android-Based Wireless Network Monitoring Mobile Application". The results achieved are in the form of a network monitoring application with the name "PRIMEWEB", using a local internet network connected to the Mikrotik RouterBoard and then distributed via Wi-Fi Access Point. The network monitoring application displays system settings, monitoring statistics, network status, and user hotspots in detail. The test results of this application have the advantage of using Mikrotik for network monitoring settings and using network traffic indicators with an independent and more efficient menu. Keywords— Android application, Mikrotik, Network, Wi-Fi